Priložnosti in ovire pri elektronskem zbiranju podatkov zdravstvene nege - Prijatelj, Vesna (Obzornik zdravstvene nege, 2005)
The article presents the opportunities and obstacles in electronic data collection in nursing, as well as the importance of nursing data standards, informatics and standard terminology evolution through decades. Important international and national projects in this field are described. The second part of the article presents present situation in Slovenia and the role of thegovernment in achievement electronic data collection in nursing. The final part of the article presents the information technology for electronic data collection in healthcare and the present situation in Slovenia in this, field,as well as propositions and steps required to achieve the goals: electronic nursing record in Slovenia.
Keywords: Computer Communication Networks; health care; informacijski sistemi; informatika; information science; Nomenclature; Nursing Care; Nursing Records; podatki; Računalniške mreže; zdravstvena informatika; Zdravstvena nega; Zdravstvena nega, kartoteke; zdravstvo